2021
DOI: 10.2147/idr.s312185
|View full text |Cite
|
Sign up to set email alerts
|

Drug- and Multidrug-Resistance Pattern of Enterobacteriaceae Isolated from Droppings of Healthy Chickens on a Poultry Farm in Southwest Ethiopia

Abstract: Background In Ethiopia, the precise attribution of animals and their food products as the sources of resistant strains and the consequences of it on human health have not yet been seriously evaluated. Therefore, the aim of this study was to assess the drug- and multidrug-resistance pattern of Enterobacteriaceae isolated from chicken droppings at Jimma University poultry farm, College of Agriculture and Veterinary Medicine, southwest of Ethiopia. Methods A cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
8
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
9
8
3
Order By: Relevance
“…(57.5%) and E. coli (34.2) observed in this study could be an indication of their superior adaptability and fitness within the harsh environment of the smallholder poultry production systems. The prevalent rates are comparable to the values previously reported for E. coli (39.0%) [18] and Salmonella spp. (59.5%) [44].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…(57.5%) and E. coli (34.2) observed in this study could be an indication of their superior adaptability and fitness within the harsh environment of the smallholder poultry production systems. The prevalent rates are comparable to the values previously reported for E. coli (39.0%) [18] and Salmonella spp. (59.5%) [44].…”
Section: Discussionsupporting
confidence: 90%
“…resistance to antibiotics may change if other conventional veterinary drugs are tested. This is because high resistance to antibiotics such as tetracycline (89.4%), cloxacillin (100.0%), and erythromycin (100.0%) [ 53 ] in Nigeria, amoxycillin (88.4%) in Uganda [ 46 ], and ampicillin (91.7%) in Ethiopia [ 18 ] has been reported in poultry. These observations are consistent with the findings of Nhung [ 54 ] in a comprehensive review where the antibiotic resistance of E. coli and Salmonella spp., among others, were found to vary with the classes and types of antibiotic drugs used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current study are in line with the findings of Bushen et al (2021) those who reported a high incidence of MDR (52.5%) in healthy chickens taken from Southwest Ethiopian farms. Noor and Poeloengan (2005) suggested that inappropriate use of antibiotics due to misdiagnosis, too harsh treatment, wrong doses, and continuous use of antibiotics as growth promoters are some important causes of multi-drug resistance.…”
Section: Antibiotic Sensitivity Testsupporting
confidence: 91%
“…P. mirabilis is inherently resistant to antibiotics, such as nitrofurantoin, polymyxin, and tigecycline [3], often exhibiting multidrug resistance under clinical settings. Previous studies have reported multidrug resistance rates of 19.3-78.13% in P. mirabilis isolated from poultry [4][5][6]. Mobilizable genetic elements (genomic islands (GIs) and Tn7-like transposons) play important roles in the capture and transmission of multidrug resistance genes in P. mirabilis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%